Lipid-lowering, antihypertensive, and antithrombotic effects of nattokinase combined with red yeast rice in patients with stable coronary artery disease: a randomized, double-blinded, placebo-controlled trial - Liu, Man; Xu, Ziyi; Wang, Zongling; Wang, Di; Yang, Mingzhe; Li, Hui; Zhang, Wei; He, Ruikun; Cheng, Huimin; Guo, Peiyu; Li, Zhongxia; Liang, Hui (Frontiers in Nutrition, 2024)
Nattokinase (NK) and red yeast rice (RYR) are both indicated for their potential in cardiovascular disease prevention and management, but their combined effects especially in coronary artery disease (CAD) are scarcely examined. This 90-day randomized, double-blind trial aims to investigate the effect of NK and RYR supplementations on cardiometabolic parameters in patients with stable CAD. 178 CAD patients were randomized to four groups: NK+RYR, NK, RYR, and placebo. No adverse effects due to the interventions were reported. In comparisons across groups, NK+RYR showed the maximum effect in reducing triglyceride (-0.39 mmol), total cholesterol (-0.66 mmol/L), diastolic blood pressure (-7.39 mmHg), and increase in high-density lipoprotein cholesterol (0.195 mmol/L) than other groups (all p for multiple groups comparison<0.01). Both NK+RYR and NK groups had significantly better-improved lactate dehydrogenase than the others (-29.1 U/L and -26.4 U/L). NK+RYR group also showed more potent reductions in thromboxane B2 and increases in antithrombin III compared to placebo (both p<0.01). These improved markers suggest that combined NK and RYR may preferably alter antithrombin and COX-1 pathways, potentially reducing thrombosis risks in CAD patients. Overall, the combined NK and RYR supplementation is safe and more effective than separately in improving cardiometabolic markers among CAD patients with multiple heart medications use.